2021
DOI: 10.1016/j.stemcr.2020.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Extraembryonic Endoderm (XEN) Cells Capable of Contributing to Embryonic Chimeras Established from Pig Embryos

Abstract: Summary Most of our current knowledge regarding early lineage specification and embryo-derived stem cells comes from studies in rodent models. However, key gaps remain in our understanding of these developmental processes from nonrodent species. Here, we report the detailed characterization of pig extraembryonic endoderm (pXEN) cells, which can be reliably and reproducibly generated from primitive endoderm (PrE) of blastocyst. Highly expandable pXEN cells express canonical PrE markers and transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
3
14
0
1
Order By: Relevance
“…We also compared our RNA sequencing data for pXEN cells with publicly available datasets from mouse XEN cells, porcine XEN-like cells, and porcine yolk sac (day 28), as well as porcine hypoblast cells of early embryos ( Figure 7 G). Hierarchical cluster analysis demonstrated that the pXEN cells derived in our lab clustered closely with the pXENpg cell lines ( Figure 7 H) derived by Park et al [ 27 ]. We chose the signaling pathway-related genes as well ( Supplementary Table S1 ) and analyzed the expression of them in these cell lines.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…We also compared our RNA sequencing data for pXEN cells with publicly available datasets from mouse XEN cells, porcine XEN-like cells, and porcine yolk sac (day 28), as well as porcine hypoblast cells of early embryos ( Figure 7 G). Hierarchical cluster analysis demonstrated that the pXEN cells derived in our lab clustered closely with the pXENpg cell lines ( Figure 7 H) derived by Park et al [ 27 ]. We chose the signaling pathway-related genes as well ( Supplementary Table S1 ) and analyzed the expression of them in these cell lines.…”
Section: Resultssupporting
confidence: 68%
“…The epiblast fraction of the primary blastocyst outgrowths from pigs usually fails to proliferate under the routine ESC derivation conditions used for rodents and primates. Instead, the cells are rapidly replaced by expanding extra-embryonic cells, which are often mistaken for epiblast-derived primed ESCs, as found in previous studies [27,36]. Therefore, the discovery of ways to inhibit the growth of the PrE and to promote the proliferation of EPI may be significant for obtaining authentic porcine ESCs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another strategy to target donor cells to the endoderm uses extraembryonic endoderm stem (XEN) cells as donor cells instead of iPSCs. XEN cells are stem cells derived from the primitive endoderm in pigs and rodents, which contribute to both extraembryonic and gut endoderm in chimeras ( Niakan et al., 2013 ; Park et al., 2021 ). Intraspecies pig chimeras generated using pig XEN donor cells resulted in donor cells restricted exclusively to the endoderm and extraembryonic structures.…”
Section: Improving In Primate Blastocyst Complementation For Hepatogenesismentioning
confidence: 99%